Quantitative easing in the euro area and SMEs access to finance: Who benefits the most? - Anne Kathrin Funk (Graduate Institute of International and Development Studies, 2019)
After the global financial crisis and during the European sovereign debt crisis, bank lending to companies in the euro area slowed down dramatically, bringing the economy close to a credit crunch. It was only after the start of the European Central Bank (ECB) quantitative easing programme in early 2015 that bank lending improved sustainably. This study analyses the impact of the ECB's Public Sector Purchase Programme (PSPP) on the access to finance of small- and medium-sized enterprises using firm-level data of the Survey on the Access to Finance of Enterprises and a fixed effects model. The analysis comprises several measures of financial access, such as credit availability, financial constraints, and interest rates. The micro-level nature of the data allows me to distinguish between aggregate and heterogeneous effects across firm size, age, sector, and country. The ECB's government bond purchases improved financial access on the aggregate euro area level and particularly in the periphery of the euro area. Hence, countries that need the most stimulus benefit the most from the PSPP.
Keywords: E44; E51; E52; E58; 330; Unconventional monetary policy; credit channel; bank lending; ECB; SME